Cyberbullying: An Overview - Rufa Mitsu; Eman Dawood (Indonesian Journal of Global Health Research, 2022)
The internet has become an integral part of modern education. Indeed, the internet has made education more approachable and ubiquitous than ever before. Despite all of the benefits that the online world has provided to children, parents, and instructors, some people exploit it for evil purposes. Cyberbullying is on the rise all over the world. In recent years, the term "cyberbullying" has gained popularity in the media, and it has been linked to several high-profile adolescent suicides. This article outlines the comprehensive overview of cyberbullying.